Air and chlorine gas corrosion of different silicon carbides analyzed by nano-Fourier-transform infrared (nano-FTIR) spectroscopy. (February 2018) - Vogel, Christian; Hermann, Peter; Kästner, Bernd; Adamczyk, Burkart; Hoehl, Arne; Ulm, Gerhard; Adam, Christian
Highlights: Chlorine gas corrosion of silicon carbides was studied by nano-FTIR spectroscopy. Nano-FTIR spectroscopy data were collected with a lateral resolution below 40 nm. High-resolution imaging provides deep insight in the interfacial layer. Abstract: The present study shows the potential of high-resolution imaging and nano-Fourier-transform infrared (nano-FTIR) spectroscopy for corrosion science. The protective oxidation layers of different chlorine-gas treated silicon carbides (SiCs) were characterized with these techniques. A nitrified SiC showed the highest resistant strength against chlorine corrosion at 1000 °C compared to the other SiCs. Nano-FTIR spectroscopy with a lateral resolution below 40 nm detected differences in the crystallinity of the bulk-SiC and in the transitional region to the protective layer. Furthermore, high-resolution imaging provides deep insight in the interfacial layer between bulk-SiC and the protective oxidation layer on sub-micrometer scale.